Family typologies of UCPR students (2021)
The article presents the results of research that was carried out during 2007 on the types of family structure of the students at UCP. The research collected and assessed data regarding type of parents’ union, family composition, level of income, education level, religious beliefs, and participation in organizations. The article presents the results concerning the first two topics.